Assumption of Moral Values By the Children and Adolescents in the Conditions of the Personality’s Psycho-physiological Self-restriction in the Extremal Situations - Khinkanina, A (KnE Life Sciences, 2018)
In the current conditions of the shortage of the ideals, romantic scarcity and difficulties in assimilating cultural values by the younger generation, it is important to study the topic of assumption of the moral patterns by the children and adolescents in the situations of physical and mental stress. L.S. Vygotsky and A.R. Luria’s ideas on the cultural and historical conditionalism of the psyche and personality’s development have become the methodological basis of the study. The empirical data were obtained during the cultural and historical event of high social significance held in Kirov every year in early June, and this event is connected with the transfer of social and cultural values from one generation to another. During the 2006–2017, the methods of observation, visual methods, an express survey suitable for studying the problem were selected and applied. The important pattern of behavior under the extremal conditions to be self-restriction, which is assumed by the children and adolescents in the process of withstanding the difficulties together with adults was studied. The results obtained showed that the emotional adaptability of children and adults in difficult life situations depends on the social environment and the significance of cultural and historical activities. The results of the embodied, unembodied observation and the express survey showed that the differences in the motivation of children and adults are not a factor of separation and are combined with the consonance of the emotional state to achieve a common goal. The data obtained open up new opportunities to explore the dynamics of self-development in the conditions of psychophysiological self-restriction and the features of the cultural values assimilation by a person and a group of people in non-standard situations. Keywords: difficult life situation, self-restriction, internal conflict, cultural values, moral values, self-development